Comparison of 2-years follow-up of optimal medical therapy versus balloon pulmonary angioplasty for inoperable chronic thromboembolic pulmonary hypertension. (14th October 2021) - Pereira, A R; Cale, R; Ferreira, F; Alegria, S; Sebaiti, S; Repolho, D; Santos, P; Vitorino, S; Pereira, H; Loureiro, M J
Abstract: Introduction: Balloon pulmonary angioplasty (BPA) has emerged as a therapeutic option for chronic thromboembolic pulmonary hypertension (CTEPH) considered ineligible for pulmonary endarterectomy (PEA). The initial publications showed very good short-term outcomes for the technique, but there are limited data regarding medium-term outcomes and its comparison with optimal medical treatment (OMT). Objectives: To evaluate and compare the medium-term outcomes of OMT versus (vs) BPA in inoperable CTEPH. Methods: Retrospective study of consecutive patients (pts) with CTEPH followed in a referral centre for Pulmonary Hypertension. Selected those pts considered ineligible for PEA and with at least 2 years of follow-up. Comparison between two treatment strategies: OMT alone [maximum tolerated doses of pulmonary vasodilator drugs (PVD), as indicated] vs BPA (pts who completed the program with or without OMT). Endpoint was a composite of all-cause death and unplanned right heart failure admission at 2-year. Results: From 62 pts, 19 pts were included (11 pts were excluded due to recent diagnosis; 32 were submitted to EAP): mean age 65.0±15.3 years, 89.5% female. At diagnosis, all pts had functional capacity limitation and elevated serum NTproBNP levels (median value 1255.0 pg/mL). Mean pulmonary arterial pressure (mPAP) was 46.2±9.3 mmHg and pulmonary vascular resistance (PVR) 15.3±8.3 Wood units (WU). Concerning treatment, 12 pts (63.2%) underwent OMT alone. These pts had higher NTproBNP levels (2670.0 vs 538.0 pg/mL, p<0.01) and PVR values (19.7±7.6 vs 9.7±5.4 WU, p=0.01) and lower CI (1.6±0.3 vs 2.4±0.5 L/min/m 2, p<0.01), at baseline; the remaining basal features didn't differ among groups (Fig.A). At 2-year follow-up, pts submitted to BPA were under PVD in 71.4% of cases with a mean of 1±0.8 drugs per patient and no difference compared to OMT group (83.3%, 1.7±0.9 drugs per patient), although oxygen therapy was higher in medical group (50% vs 0%, p=0.04). A significant overall improvement was observed in BPA group (Table – A): all pts were in functional class I (p<0.01), no one had right ventricular dysfunction (p<0.01) and mPAP decreased to 25.1±6.7 mmHg (p=0.01) and RVP to 2.9±0.8 WU (p=0.01). Inversely, no change was observed in pts under OMT alone (p>0.05 in all, Table – A). Endpoint rate was 31.6% with all adverse events occurring in the OMT group (50% vs 0%, p=0.04). After adjustment by Cox regression, no difference in baseline or follow-up features besides treatment influenced the outcome. Kaplan-Meier analysis (Graphic – B) confirmed significant benefit of BPA in 2-year outcome occurrence (long rank 4.6, p=0.03). Conclusions: BPA strategy seems to improve medium-term functional capacity, right ventricular function and haemodynamics and decrease oxygen therapy dependence in inoperable CTEPH. Pts under OMT alone have a poor prognosis. These data encourage the development and implementation of the technique for inoperable CTEPH. Funding Acknowledgement: Type of funding sources: None.